Penerapan Token Ekonomi pada Pasien Gangguan Jiwa dengan Ketidakpatuhan Minum Obat - Meilena, Cahya; Amin, Muhammad Khoirul; Astuti, Retna Tri; Pinilih, Sambodo Sriadi (Universitas Muhammadiyah Magelang, 2025)
Background: Mental disorders are conditions that affect a person's thoughts, feelings, and behavior, often disrupting daily activities, including adherence to prescribed treatment. Non-adherence to medication is one of the leading causes of relapse and re-hospitalization in patients with mental disorders. One behavioral approach that can be applied to improve adherence is the token economy method. Objective: The aim of this case study is to apply nursing care for patients with mental disorders who experience medication non-adherence by implementing a token economy intervention. Methods: This study used a descriptive case study design. The researcher explored the real-life experiences of patients through direct observation, interviews, and document analysis. The nursing process was guided by the Indonesian Nursing Diagnosis Standards (SDKI), Nursing Outcomes Standards (SLKI), and Nursing Intervention Standards (SIKI), along with the Morisky Medication Adherence Scale (MMAS-8) as a measurement tool. The subjects were two male clients aged 40–45 years with low adherence scores and no medication supervisors. The intervention was conducted over six sessions in two weeks, providing star-shaped tokens each time the clients took their medication, which could later be exchanged for personal items. Results: The intervention resulted in an increase in MMAS-8 scores from 4 (low) to 7 (moderate) in both clients. Improvements were also observed in all adherence indicators based on SLKI. Clients showed higher motivation, improved behavior, and a reduction in psychiatric symptoms. Conclusion: The application of the token economy method as a behavioral therapy is effective in increasing medication adherence in clients with mental disorders. This intervention helps establish positive routines and provides meaningful motivation for clients.